Unheard Playful Voices: Margaret Atwood᾽s Grace Marks as an (Reliably) Unreliable Narrator - Fonfárová, Vladimíra (American & British Studies Annual, 2015)
The unreliable narrator, a category with a question mark since the 1960s when it was identified by Wayne C. Booth, has been a challenge for many literary theorists including James Phelan, Monika Fludernik and Ansgar Nünning to name just a few. In the Czech Republic, Tomáš Kubíček attempted to address the issue of an unreliable narrator in his monograph Vypravěč, kategorie narativní analýzy [The Narrator, Categories of Narrative Analysis, 2007]. Drawing mostly on the theories of Nünning and Phelan, Kubíček provides his own definition, one that resolves several problematic issues with which his predecessors struggled. This paper aims to apply Kubíček’s theory of the unreliable narrator to Margaret Atwood’s historiographic metafiction Alias Grace (1996). Grace Marks, the novel’s homodiegetic narrator, has been frequently referred to as unreliable by numerous scholars, including Sharon R. Wilson and Coral Ann Howells. She appears to be an ideal subject for analyzing reliability, as she is a convicted criminal with (claimed) amnesia, therefore it seems natural that the reader should be wary of the facts she presents. However, in the light of Kubíček’s theory, the matter of Grace’s unreliability is not necessarily so obvious and simple. Obtaining a satisfactory answer to the question “Did Grace Marks commit the murders she was imprisoned for?” may be just as difficult as obtaining the answer to a question whether Atwood’s novel presents an unreliable narrator or not.